Development of Digital Teaching Materials with a STREAM Approach on Biotechnology Materials to Improve Students’ Science Literacy and Bioentrepreneurship Interes - Dewi, Bita Afriyati; Ellianawati, Ellianawati; Widiyatmoko, Arif (Unnes Science Education Journal, 2025)
The development of digital teaching materials using STREAM approach is need ed on biotechnology material due to lack of digital teaching materials, low scientific literacy and lack of bioentrepreneurship material. This research aims to present the characteristics, validity and effectiveness of digital teaching materials using the STREAM approach on biotechnology to increase students’ scientific literacy and interest in bioentrepreneurship. The results of questionnaire analysis using aiken-V show that digital teaching materials received valid scores from 4 validators, namely religious experts with score of 1, entrepreneur experts with score of 0.94, material experts with score of 0.95 and media experts with score of 0.98. The results of students’ scientific literacy are shown by the N-gain value, namely 0.71 in the high category. The results of students’ bioentrepreneurship interest are shown by the N-gain, namely 0.73 in the high category. Biology teacher response results obtained a percentage of 92% with very good criteria. Students’ responses after using digital teaching materials also received positive responses. Based on the results of this research, it can be concluded that digital teaching materials with the STREAM approach on biotechnology material can be used in learning to increase students’ scientific literacy and bioentrepreneurship interest.